Autism detection based on MRI images using Deep Learning - Mostafa, Sadab; Noshin, Tasnim Hoque; Xenon, Zihadul Karim; Arbi, Jimmati (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.